1995
DOI: 10.1161/01.hyp.25.4.560
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Activation in Obese Normotensive Subjects

Abstract: Human obesity is characterized by profound alterations in the hemodynamic and metabolic states. Whether these alterations involve sympathetic drive is controversial. In 10 young obese subjects (body mass index, 40.5 +/- 1.2 kg/m2, mean +/- SEM) with normal blood pressure and 8 age-matched lean normotensive control subjects, we measured beat-to-beat arterial blood pressure (Finapres technique), heart rate (electrocardiogram), postganglionic muscle sympathetic nerve activity (microneurography at the peroneal ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
370
4
32

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 534 publications
(437 citation statements)
references
References 27 publications
31
370
4
32
Order By: Relevance
“…In a large subgroup of obese patients, sympathetic activity is increased even at rest. 15,28 Our analysis has several limitations. The analysis was retrospective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large subgroup of obese patients, sympathetic activity is increased even at rest. 15,28 Our analysis has several limitations. The analysis was retrospective.…”
Section: Discussionmentioning
confidence: 99%
“…12 The complex interaction of peripheral and central nervous mechanisms makes it difficult to predict the cardiovascular response to sibutramine in patients with altered sympathetic activity, such as obese hypertensives. 15 A recent post marketing surveillance study suggested a significant decrease in blood pressure with sibutramine in obese hypertensives. 16 We pooled data from two recent clinical trials to determine the effect of sibutramine treatment on blood pressure in obese subjects with different degrees of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Microneurograhic techniques, a direct method of measuring increased SNS activity, provide evidence of high muscle SNS activity in obese subjects. 4 High-caloric intake increases norepinephrine turnover in peripheral tissues, raises resting plasma norepinephrine concentrations-an indirect measurement of SNS activity-and amplifies the rise of plasma norepineprhine in response to stimuli such as upright posture. 5 High dietary content in fat and carbohydrate has been suggested to acutely stimulate peripheral a 1 -and b-adrenergic receptors, leading to elevated sympathetic activity and hypertension.…”
Section: Sympathetic Activation In Obesitymentioning
confidence: 99%
“…A reduced sensitivity of the arterial baroreflex manifested as a diminished response in heart rate to BP changes may occur in long-standing hypertension and obesity, 4 presumably because of various mechanisms, including a concomitant increase in central sympathetic outflow and the effects of arteriosclerotic lesions leading to an increased stiffness of the large arteries in which the receptors are located. We have earlier reported an increased carotid arteries intima media thickness in obese subjects independently of the BP levels, even in a normotensive BP range, suggesting an early course of the atherosclerotic process in obesity.…”
Section: Sympathetic Activation In Obesitymentioning
confidence: 99%
See 1 more Smart Citation